2007
DOI: 10.2337/dc06-2581
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Overall Diet Quality and Risk of Type 2 Diabetes in Women

Abstract: OBJECTIVE -The aim of this article was to assess the association between the Alternate Healthy Eating Index (AHEI) and risk of type 2 diabetes in women.RESEARCH DESIGN AND METHODS -A total of 80,029 women aged 38 -63 years in the Nurses' Health Study were followed from 1984 to 2002. The AHEI score was computed from dietary information collected from five repeated food frequency questionnaires administered between 1984 and 1998. Relative risks (RRs) for type 2 diabetes were calculated using Cox proportional haz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
118
4
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(132 citation statements)
references
References 46 publications
9
118
4
1
Order By: Relevance
“…16 Several different scoring systems have been reported in an effort to quantify the extent of adherence to the Mediterranean dietary pattern. [24][25][26][27][28][29] Crosscultural variability in the application of the Mediterranean diet limits the development of precise associations or conclusive findings on the specific benefits in risk factor reduction, including effects on serum lipids.…”
Section: Developing Dietary Pattern Guidelinesmentioning
confidence: 99%
“…16 Several different scoring systems have been reported in an effort to quantify the extent of adherence to the Mediterranean dietary pattern. [24][25][26][27][28][29] Crosscultural variability in the application of the Mediterranean diet limits the development of precise associations or conclusive findings on the specific benefits in risk factor reduction, including effects on serum lipids.…”
Section: Developing Dietary Pattern Guidelinesmentioning
confidence: 99%
“…Overall diet can be assessed by using composite evidence-based scores that comprise multiple nutrients and food groups, such as the Alternate Healthy Eating Index (AHEI). There is strong evidence of associations between higher AHEI (which reflects better diet quality, based on current evidence) and lower risk of diabetes, CVD, and MetS (11)(12)(13)(14)(15). Some of these studies reported stronger associations with chronic disease risk with the AHEI than with other diet quality scores (12,13,15).…”
Section: Introductionmentioning
confidence: 95%
“…There is strong evidence of associations between higher AHEI (which reflects better diet quality, based on current evidence) and lower risk of diabetes, CVD, and MetS (11)(12)(13)(14)(15). Some of these studies reported stronger associations with chronic disease risk with the AHEI than with other diet quality scores (12,13,15). This is likely because the AHEI includes specific foods and nutrients, such as legumes, sugar-sweetened beverages, and red or processed meats, which have a role in the development of chronic disease but are absent or incorporated within general food groups in other diet scores (15).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Healthful dietary patterns characterised by high consumption of fruit and vegetables, whole grains, fish and poultry may delay the progression to type 2 diabetes, 13,15 whereas Western dietary patterns have been demonstrated to increase risk. 16 Likewise, a variety of diet quality tools that measure adherence to dietary guidelines have demonstrated that a high-diet quality, representing alignment with national dietary guidelines, is inversely associated with obesity, blood lipids, hyperglycaemia and hyperinsulinaemia, as well as all-cause mortality and indices of selfrated health.…”
Section: Introductionmentioning
confidence: 99%